Supplementary Information and Figures for Manuscript - Hayden Dalton (2022)
This file contains Supporting Information Figures S1 to S6 and the accompanying captions and references, which supplement the article “ Geodynamic and isotopic constraints on the genesis of kimberlites, lamproites and related magmas from the Finnish segment of the Karelian craton ”. Submitted to Geochemsitry, Geophysics, Geosystems on 30th December 2021